Meta-Analysis on the Efficacy and Safety of Hyperbaric Oxygen as Adjunctive Therapy for Vascular Dementia - You, Qiang; Li, Lan; Xiong, Su-qin; Yan, Yu-fen; Li, Dan; Yan, Na-na; Chen, Hong-ping; Liu, You-ping (Frontiers in Aging Neuroscience, 2019)
Background: Vascular dementia (VD) is a common type of disease in the elderly. Numerous clinical trials have suggested that hyperbaric oxygen is an effective and safe complementary therapy for aging-related disorders. However, there is no reliable systematic evidence regarding hyperbaric oxygen therapy (HBOT) for the treatment of VD. Therefore, we performed a meta-analysis to evaluate the clinical efficacy and safety of HBOT in treating VD. Methods: We methodically retrieved the clinical studies from eight databases (PubMed, Cochrane Library, Embase, Web of Science, Sino-Med, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and WanFang) from their inception to November 2018. RevMan 5.3.5 was used for quality assessment and data analysis. Stata 15.1 was employed for publication bias detection and sensitivity analysis. Results: Twenty-five randomized clinical trials (RCTs) involving 1,954 patients met our inclusion criteria. These articles researched the HBOT + oxiracetam + conventional therapy (CT) vs. oxiracetam + CT (n = 13), HBOT + butylphthalide +CT vs. butylphthalide + CT (n = 5), HBOT + donepezil + CT vs. donepezil + CT (n = 4), HBOT + nicergoline + CT vs. nicergoline + CT (n = 2) and HBOT + CT vs. CT (n = 1). The results indicated that additional HBOT strikingly improved the Mini-Mental State Examination (MMSE) (MD = 4.00; 95% CI = 3.28–4.73; P < 0.00001), activities of daily living (ADL) (MD = −5.91; 95% CI = −6.45, −5.36; P < 0.00001) and ADL by Barthel index (BADL) (MD = 13.86; 95% CI = 5.63–22.10; P = 0.001) and increased the total efficacy rate (TEF) (OR = 4.84, 95% CI = 3.19–7.33, P < 0.00001). The adverse events rates were not statistically significant between the HBOT and CT groups (OR = 0.85, 95% CI = 0.26–2.78, P = 0.79). Conclusion: In view of the effectiveness and safety of HBOT, the present meta-analysis suggested that HBOT can be recommended as an effective and safe complementary therapy for the treatment of VD. Protocol Registration: PROSPERO (ID: CRD42019117178). Available online at: http://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42019117178.